2011
DOI: 10.1111/j.1748-5827.2010.01028.x
|View full text |Cite
|
Sign up to set email alerts
|

Diseases in pet degus: a retrospective study in 300 animals

Abstract: This is the first study to describe the disease prevalence in two age groups of pet degus. The majority of diseases were caused by improper diet, self-mutilation and improper handling; as such client education is necessary to avoid such a high disease prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 38 publications
(48 reference statements)
3
61
1
Order By: Relevance
“…Degus also require a specialized diet low in sugar to prevent diabetes. A study of 300 degus presented to a veterinary clinic found that most disease in the species was caused by poor husbandry and handling, including acquired dental disease, alopecia caused by fur chewing (self-mutilation), cataracts, trauma, diabetes mellitus, and hyperthermia [86]. It was concluded that owners’ knowledge levels were not sufficient to properly care for their animals in most cases.…”
Section: Rabbits and Rodentsmentioning
confidence: 99%
“…Degus also require a specialized diet low in sugar to prevent diabetes. A study of 300 degus presented to a veterinary clinic found that most disease in the species was caused by poor husbandry and handling, including acquired dental disease, alopecia caused by fur chewing (self-mutilation), cataracts, trauma, diabetes mellitus, and hyperthermia [86]. It was concluded that owners’ knowledge levels were not sufficient to properly care for their animals in most cases.…”
Section: Rabbits and Rodentsmentioning
confidence: 99%
“…The degu (Octodon degus) is a caviomorph rodent, a member of the family Octodontidae and is commonly kept as a pet or laboratory animal (Jekl et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The most common diseases reported in a survey of 300 privately owned degus were dental conditions (Jekl et al, 2011d). Most common dental conditions are malocclusion of either the molars or incisors (Jekl et al, 2011a,b,d).…”
Section: Diseasesmentioning
confidence: 99%
“…Other commonly occurring non-infectious diseases include cataracts (Worgul and Rothstein, 1975;Jekl et al, 2011d). Cataract formation may be congenital or acquired as a side-effect of diabetes development.…”
Section: Diseasesmentioning
confidence: 99%
See 1 more Smart Citation